The reality of implementing kindergarten (KG) female teachers for the standard of language development and early knowledge of reading and writing in teaching from the perspective of female educational supervisors in Riyadh - Alarifi, Hilalah Mohmmed; Aldoheman, Helah Khalaf (Journal of Curriculum and Teaching Methodology, 2024)
This research endeavors to assess the implementation status of language development standards and early literacy skills among female kindergarten (KG) teachers in Riyadh, as perceived by female educational supervisors. A survey method was employed, with a sample comprising 37 KG educational supervisors. Data were gathered using a questionnaire structured around three primary domains: listening, speaking, and reading and writing. The findings indicate the following key points: (1) Female KG teachers demonstrate a high level of proficiency in implementing language development standards and early literacy skills, with listening and speaking skills ranking highest at 89.3%, followed by reading skills at 86.6%, and writing skills at 84.9%. (2) Educational supervisors perceive a very high degree of proficiency among female KG teachers in implementing listening and speaking skills in alignment with developmental learning standards. (3) Similarly, a very high degree of proficiency is observed in the implementation of reading skills. (4) Female KG teachers exhibit a very high level of proficiency in implementing writing and speaking skills in accordance with developmental learning standards, as perceived by educational supervisors.